Tax benefits as a basic component of the investment tax expenditure management system in the region - S. N. Rukina; K. A. Gerasimova; A. S. Takmazyan; K. N. Samoylova (Вестник университета)
The article investigates tax and budget components of the investment tax expenditure management system in the region with a focus on tax benefits and tax powers of the authorities. The information base of the study is the federal and regional legislation, publications in scientific journals, open data of the Ministry of Finance of the Russian Federation, and the Government of the Rostov Oblast. Following general scientific methods of knowledge were used as a methodological basis: comparison, systematic logical and semantic analysis, synthesis of theoretical and practical materials. It allowed to substantiate expediency of significant changes in tax component of the investment tax expenditure management system. The definition of tax exemption, which has not changed during the 25-year period, has been clarified. Tax powers of public authorities of the Russian constituent entities on property and profit taxes of organizations have been expanded. The abandonment of tax costs assessment has been carried out by their supervisors in favor of software product of the Federal Tax Service of Russia developed jointly with the Ministry of Finance of Russia. The results of the study can be used by the authorities when developing proposals to improve tax and budget legislation.